Physicochemical and Biochemical Properties of Coconut Water Across Maturity Stages in Aromatic Dwarf, Catigan Dwarf, and Laguna Tall Cultivars - Chester Deocaris; Dina Masa (International Coconut Community Journal, 2025)
This study examines the biochemical and physicochemical properties of coconut water from three coconut (Cocos nucifera Linn.) cultivars—Aromatic Dwarf (AROD), Catigan Dwarf (CATD), and Laguna Tall (LAGT)—across maturity stages ranging from 5 to 12 months. Key parameters analyzed included pH, total soluble solids (TSS), specific gravity, glucose, protein, and electrolyte composition (sodium, potassium, calcium, magnesium, and chloride). Results revealed significant variations influenced by both cultivar and maturity. AROD exhibited the highest glucose and TSS levels at early maturity, making it ideal for naturally sweet beverages. LAGT maintained stable electrolyte concentrations, supporting its application in rehydration formulations. CATD had the highest calcium and magnesium levels, suggesting potential benefits for bone and muscle health. Trends in pH and specific gravity provided insights into compositional shifts during maturation. These findings highlight the diverse functional properties of coconut water across cultivars, offering valuable insights for optimizing harvest timing, product formulation, and market positioning in the functional beverage and nutraceutical industries.